2014
DOI: 10.3329/jbau.v11i1.18204
|View full text |Cite
|
Sign up to set email alerts
|

Integrated nutrient management on soil fertility, growth and yield of tomato

Abstract: To evaluate the effects of integrated nutrient management on growth and yield of BARI tomato-14 and soil fertility, a pot experiment was conducted in the net house of the department of Agricultural Chemistry of Bangladesh Agricultural University, Mymensingh during the period from October 2011 to April 2012. The experiment was laid out in a completely randomized design with 11 treatments and 3 replications. Treatments were control, RDCF100, 75% RDCF, 50% RDCF, 75% RDCF + PM2 t /ha, 75% RDCF + RS3 t /ha, 75% RDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
5
7
0
Order By: Relevance
“…(2016) also observed that the number of leaves plant −1 was higher with the increased S rates up to 30 kg ha −1 . This finding is also similar with the previous reports for the increased leaf number of different crops with S fertilization ( Islam et al., 2013 ; Lalitha and Gopala 2004 ).
Figure 2 Effects of different levels of sulphur on the number of leaves of Aloe vera L. at different days after transplanting (DAT).
…”
Section: Resultssupporting
confidence: 93%
“…(2016) also observed that the number of leaves plant −1 was higher with the increased S rates up to 30 kg ha −1 . This finding is also similar with the previous reports for the increased leaf number of different crops with S fertilization ( Islam et al., 2013 ; Lalitha and Gopala 2004 ).
Figure 2 Effects of different levels of sulphur on the number of leaves of Aloe vera L. at different days after transplanting (DAT).
…”
Section: Resultssupporting
confidence: 93%
“…It is, therefore, imperative that if the number of branches plant -1 is higher, the numbers of leaves are expected to be higher; ultimately the leaf yield will be higher. This finding is also similar with the results of Islam et al (2013) who reported that number of branch plant -1 was increased due to application of different doses of inorganic fertilizers. These growth parameters might have possibly contributed positively to the higher leaf yield with higher N application.…”
Section: Discussion Leaf Yield and Yield Attributessupporting
confidence: 82%
“…Nasrin (2008) obtained higher values of yield and yield parameters of stevia with N @ 250 kg ha -1 . This finding is also similar with the results of Islam et al (2013) who reported that number of leaves plant -1 in tomato was increased due to application of different doses of inorganic fertilizers. Leaf area is an important growth indices determining the capacity of plant to trap solar energy for photosynthesis and has marked influence on the growth and yield of plant.…”
Section: Discussion Leaf Yield and Yield Attributessupporting
confidence: 82%
“…Kawatani et al, (1980) had also reported increased number of branches and leaves plant -1 of stevia with higher inorganic nutrition in Japan. This finding is also similar with the results of Islam et al, (2013) who reported that number of leaves plant -1 in tomato was increased due to the application of different doses of inorganic fertilizers. Aladakatti et al, (2012) found that plant height of stevia at harvest was significantly influenced by higher levels of nitrogen, phosphorus and potassium which in turn were responsible for higher number of branches plant -1 and number of leaves plant -1 resulting into higher leaf yield.…”
Section: Leaf Numbersupporting
confidence: 82%